Strategi Integrasi Maqashid Syariah Dalam Kebijakan Good Corporate Governance Di Perbankan Syariah - Iqbal, M.; Ritonga, Zernita Sari; Nawrah, Hilwatun; Siregar, Muhammad Maulana (STAI Denpasar Bali, 2024)
Maqashid sharia is the goal and secret that has been established by Allah SWT as the creator of legal rules that humans must obey as creatures who have been created with the aim of being caliphs on this earth. Good Corporate Governance is a system of good corporate governance in managing the company's resources efficiently, effectively, economically and productively using the principles of openness, accountability, responsibility, independence and fairness in an effort to achieve the goals of establishing the company. The aim of this research is to determine the integration strategy for maqashid sharia in good corporate governance policies in maintaining sharia banking operations. The research method uses a qualitative approach with a literature study type of research. The results of the research are the application of maqashid sharia values ​​in products and operational activities in sharia banking, namely protecting religion, protecting the soul, protecting the mind of both the customer and the bank, protecting property and protecting offspring. In order to increase sharia maqashid values ​​in accordance with the principles that must be implemented by sharia banking, good corporate governance policies must carry out two stages, namely: The need to make the rules and recognition mechanism (endorsement) from the fatwa authority more effective and the supervisory system that supervises it more effective. Bank financial transactions are in accordance with the fatwa issued by the banking fatwa authority.